2018
DOI: 10.1055/a-0723-3544
|View full text |Cite
|
Sign up to set email alerts
|

Early Growth Hormone Intervention Improves Glucose Metabolism in Adult Rats Born Small for Gestational Age

Abstract: Background Small for gestational age (SGA) due to intrauterine malnourishment is closely related to metabolic syndrome and type 2 diabetes mellitus. Growth Hormone (GH) treatment has been demonstrated to influence metabolic parameters and islet function of SGA individuals. The present study demonstrates the effects of early GH treatment on glucose tolerance and expression of pancreatic duodenal homeobox 1 (Pdx1) of SGA rats during adulthood. Methods SGA rat model was induced by restricting food intake during p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…We found that 3 differentially methylated genes ( PDX1, DECR1 and GNAS ) had been previously associated with SGA, [ 21 , 22 ] suggesting (at least in part) the changes of some genes in SGA and LGA were similar in some pathways and regulatory effects. In this study, the largest methylation difference was demonstrated in the promoter region of the FKBP11 gene.…”
Section: Discussionmentioning
confidence: 89%
“…We found that 3 differentially methylated genes ( PDX1, DECR1 and GNAS ) had been previously associated with SGA, [ 21 , 22 ] suggesting (at least in part) the changes of some genes in SGA and LGA were similar in some pathways and regulatory effects. In this study, the largest methylation difference was demonstrated in the promoter region of the FKBP11 gene.…”
Section: Discussionmentioning
confidence: 89%
“…GH deficiency showed small mandibles [43]. Rats that were small for gestational age showed reduced body weight with increased HDAC and could be treated by exogenous GH administration [44]. The administration of trichostatin A, which is an HDACi, increased GH-mRNA expression level in pituitary cells [45].…”
Section: Discussionmentioning
confidence: 99%
“…A rat model of SGA was established in animals under maternal undernutrition during pregnancy as previously described ( 21 , 22 ). In brief, adult SPF-grade Sprague-Dawley female (n=15) and male (n=5) rats were mated overnight.…”
Section: Methodsmentioning
confidence: 99%